A critical evaluation based on Lattice Boltzmann method of nanoscale thermal behavior inside MOSFET and SOI-MOSFET. (September 2021) - Zobiri, Oussama; Atia, Abdelmalek; Arıcı, Müslüm
Abstract: In recent years, the world has witnessed a huge technological revolution in terms of manufacturing electronic devices and reducing their size, which has reached nanoscale. Metal Oxide Semiconductor Field Effect Transistor (MOSFET) is one of these devices. However, with its downsizing, it affects the efficiency of its associated devices due to the generated heat. In this paper, two-dimensional heat transfer inside a Silicon on Insulator (SOI) MOSFET and traditional MOS transistor is investigated using the Lattice Boltzmann Method (LBM) . It was found that the temperature reaches 340 K and 332 K for SOI-MOSFET and MOSFET at a Knudsen number ( Kn= Λ /L c ) of 10, respectively, while the heat flux reaches 21.5 × 10 11 W/m 2 for SOI transistor and 18.7 × 10 11 W/m 2 for MOS device. The insulating layer (SiO 2 )in the SOI transistor restrains heat release in the channel region. So, the conventional MOSFET at Kn =10 is thermally more stable, compared to SOI-MOSFET. Graphical abstract: Highlights: A delicate LBM is utilized to study the thermal transport in MOSFET and SOI-MOSFET. The temperature reaches a saturation at 15 ps. Silicon on insulator buried layer acts like a thermal cage. The increases in the length of channel region causes an increase in the heat inside devices. The conventional MOSFET is more thermally stable compared with SOI MOSFET.